Feasibility Analysis Of Sharia-Based Local Productive Enterprises In Phatnawitya School Yala, Thailand - Dwiyana, Anisyah Kesuma; Syahrul Amsari (Al Tijarah, 2024)
The community around Phatnawitya Yala School has a variety of local potentials that include agriculture, fisheries, handicrafts, and service sectors. This region is known as one of the high-quality rice-producing areas, with an agricultural system that is still traditional but has the potential to be developed into a modern agribusiness. This research analyzes the feasibility of sharia-based local businesses in the Pahtna Witya Yala School community in Thailand". The research method used is qualitative descriptive. With data collection techniques through observation, interviews, documentation, and literature studies. Data analysis techniques are carried out by data reduction, data presentation, and data retrieval. The validity of the data in this study is guaranteed through the application of triangulation. The results of the study show that productive businesses based on local potential and sharia principles are worthy of development and have a real impact on improving the welfare of the people of Pahtna Witya Yala Scholl Thailand.